Long-term whole-body vibration induces degeneration of intervertebral disc and facet joint in a bipedal mouse model - Jin, Lin-Yu; Yin, Hong-Lin; Xu, Yi-Qiong; Xu, Shuai; Song, Xiao-Xing; Luo, Yan; Li, Xin-Feng (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Whole body vibration (WBV) has been used to treat various musculoskeletal diseases in recent years. However, there is limited knowledge about its effects on the lumbar segments in upright posture mice. This study was performed to investigate the effects of axial Whole body vibration on the intervertebral disc (IVD) and facet joint (FJ) in a novel bipedal mouse model. Methods: Six-week-old male mice were divided into control, bipedal, and bipedal + vibration groups. Taking advantage of the hydrophobia of mice, mice in the bipedal and bipedal + vibration groups were placed in a limited water container and were thus built standing posture for a long time. The standing posture was conducted twice a day for a total of 6 hours per day, 7 days per week. Whole body vibration was conducted during the first stage of bipedal building for 30 min per day (45 Hz with peak acceleration at 0.3 g). The mice of the control group were placed in a water-free container. At the 10th-week after experimentation, intervertebral disc and facet joint were examined by micro-computed tomography (micro-CT), histologic staining, and immunohistochemistry (IHC), and gene expression was quantified using real-time polymerase chain reaction. Further, a finite element (FE) model was built based on the micro-CT, and dynamic Whole body vibration was loaded on the spine model at 10, 20, and 45 Hz. Results: Following 10 weeks of model building, intervertebral disc showed histological markers of degeneration, such as disorders of annulus fibrosus and increased cell death. Catabolism genes’ expression, such as Mmp13, and Adamts 4/5, were enhanced in the bipedal groups, and Whole body vibration promoted these catabolism genes’ expression. Examination of the facet joint after 10 weeks of bipedal with/without Whole body vibration loading revealed rough surface and hypertrophic changes at the facet joint cartilage resembling osteoarthritis. Moreover, immunohistochemistry results demonstrated that the protein level of hypertrophic markers (Mmp13 and Collagen X) were increased by long-durationstanding posture, and Whole body vibration also accelerated the degenerative changes of facet joint induced by bipedal postures. No changes in the anabolism of intervertebral disc and facet joint were observed in the present study. Furthermore, finite element analysis revealed that a larger frequency of Whole body vibration loading conditions induced higher Von Mises stresses on intervertebral disc, contact force, and displacement on facet joint. Conclusion: The present study revealed significant damage effects of Whole body vibration on intervertebral disc and facet joint in a bipedal mouse model. These findings suggested the need for further studies of the effects of Whole body vibration on lumbar segments of humans.